Study of color alterations in European oak wood during vacuum drying - Sandoval Torres, Sadoth; Jomaa, Wahbi; Marc, Françoise; Puiggali, Jean-Rodolphe (Instituto de Ecología, A.C., 2016)
An analysis of the mechanisms of discoloration in oak wood during plain vacuum drying allowed us to identify three mechanisms of discoloration. These include degradation of hemicelluloses, oxidation of tannins and release of volatile organic components. We studied the alterations to the material by measuring color changes, determining the antioxidant potential and analyzing the surface using infrared spectroscopy. Three vacuum drying conditions were applied (46 °C, 61 °C and 70 °C at pressure levels of 6 kPa - 10 kPa (60 mBar - 100 mBar). Despite the difficulty of studying and establishing the role of the extractives in changes in wood color during vacuum drying, we found relationships between the drying temperature, antioxidant potential and C=O peak intensities in the infrared spectra. By the oxidation and hydrolysis reactions, certain chemical compounds are modified. In addition, the presence of water and air accelerates the formation of organic acids (acetic acid). These acids catalyze the hydrolysis of hemicelluloses. The increase in color saturation and brightness can be related to the thermal degradation of extractives (mainly the ellagitannins).